Accelerated Domestication of New Crops: Yield is Key. (18th May 2022) - Luo, Guangbin; Najafi, Javad; Correia, Pedro M P; Trinh, Mai Duy Luu; Chapman, Elizabeth A; Østerberg, Jeppe Thulin; Thomsen, Hanne Cecilie; Pedas, Pai Rosager; Larson, Steve; Gao, Caixia; Poland, Jesse; Knudsen, Søren; et al.
Abstract: Sustainable agriculture in the future will depend on crops that are tolerant to biotic and abiotic stresses, require minimal input of water and nutrients and can be cultivated with a minimal carbon footprint. Wild plants that fulfill these requirements abound in nature but are typically low yielding. Thus, replacing current high-yielding crops with less productive but resilient species will require the intractable trade-off of increasing land area under cultivation to produce the same yield. Cultivating more land reduces natural resources, reduces biodiversity and increases our carbon footprint. Sustainable intensification can be achieved by increasing the yield of underutilized or wild plant species that are already resilient, but achieving this goal by conventional breeding programs may be a long-term prospect. De novo domestication of orphan or crop wild relatives using mutagenesis is an alternative and fast approach to achieve resilient crops with high yields. With new precise molecular techniques, it should be possible to reach economically sustainable yields in a much shorter period of time than ever before in the history of agriculture.